Effects of Catfi sh Oil Intervention on Lipid Profi le in Female Aged Cynomolgous Monkey (Macaca fascicularis) - Iskari Ngadiarti; Clara M. Kusharto; Dodik Briawan; Sri Anna Marliyati; Dondin Sajuthi (Penerbit UKM, 2014)
Degenerative process is an accumulation of free radicals that can lead to a variety of changes in the cell. This aim of the study to see the effects of different dietary lipid intervention on lipid profi le and lipid peroxidation in female aged cynomolgus monkey. Twelve female Cynomolgus monkey (Macaca fascicularis) were randomly divided into 4 dietary groups of three animals. Animals were held in individual cages and placed in the position where they can interact individually. They were given a normal fat diet with 2% cholesterol and 3% of fat from soybean oil and 9% of lipid as beef tallow (BFT), catfi sh oil (CFO), fermented catfi sh oil (FCFO) and soybean oil (SBO). Evaluation of their body weights, serum lipid profi le and cholesterol content consumption were done monthly except an index of lipid peroxidation were performed before and after 12 weeks intervention. Animal group that consumed the feed more than 82% has body weight gain, such as CFO and BFT. On the other side, animal group that consumed less than 70% has body weight loss, such as FCFO. There was no effect (p > 0.05) of the experimental diets on decreasing triglyceride levels and increasing HDL cholesterol level. Cynomolgous given BFT, CFO, and FCFO diet for 3 months showed signifi cantly increased (p < 0.05) in total cholesterol and LDL cholesterol level, but the monkeys fed with SBO showed lower levels. Statistically, All of diet interventions do not signifi cantly affect on lipid peroxidation in LDL (p < 0.05). In general it can be concluded that catfi sh oil signifi cantly cause elevated levels of total cholesterol and LDL cholesterol in blood serum, but not in the HDL plasma.